Design of four-layer tri-wavelength silica antireflective coatings with vector method containing absentee layer - Wensheng Lin; Xiaoyong Hu; Xueqing You; Lianghong Yan; Xinxiang Zhang; Hanxian Chen (Results in Physics, 2019)
A four-layer tri-wavelength silica antireflective (AR) coating with 100% transmittance simultaneously at 1064 nm, 532 nm and 355 nm was designed based on the vector method combined with absentee layer. The type of this AR coating is λ/2-λ/4-λ/2-λ/4 (λ0 = 532 nm): 1.0|L A1 H A2|1.46 with nL = 1.19, nA1 = 1.31, nH = 1.44 and nA2 = 1.33. Keywords: Antireflective coating, Tri-wavelength, Vector design, Absentee layer